2021
DOI: 10.7759/cureus.16407
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case of Budd-Chiari Syndrome in a Young Child: A Diagnostic Conundrum

Abstract: Budd-Chiari syndrome (BCS) is an uncommon vascular disorder in which venous thrombosis prevents the venous outflow of the liver. The obstruction is primarily at the level of hepatic veins and inferior vena cava.Here, we present a case of a two-and-a-half-year-old male child who presented with complaints of abdominal distension for two months and fever and watery diarrhea for one month. Physical examination showed the patient was anemic with palmar erythema. He was started on an empirical treatment of cefotaxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Medical Science 27, e181ms2838 (2023) 6 of 9 The causes of Budd-Chiari syndrome are inherited and acquired state of hypercoagulable. Inherited causes such as protein C, S deficiency, factor V Leiden mutation and anti-thrombin III deficiency are the common causes of hepatic vein thrombosis which results in BCS (Timsaal et al, 2021). Acquired causes such as polycythaemia Vera, paroxysmal nocturnal haemoglobinuria and myelofibrosis, accounts for >50% of BCS cases.…”
Section: Case Report | Open Accessmentioning
confidence: 99%
“…Medical Science 27, e181ms2838 (2023) 6 of 9 The causes of Budd-Chiari syndrome are inherited and acquired state of hypercoagulable. Inherited causes such as protein C, S deficiency, factor V Leiden mutation and anti-thrombin III deficiency are the common causes of hepatic vein thrombosis which results in BCS (Timsaal et al, 2021). Acquired causes such as polycythaemia Vera, paroxysmal nocturnal haemoglobinuria and myelofibrosis, accounts for >50% of BCS cases.…”
Section: Case Report | Open Accessmentioning
confidence: 99%
“…
Budd-Chiari syndrome (BCS) is an infrequent occurrence, predominantly found in south-eastern Asia with an incidence of one per one million across the world annually. 1,2 Primary BCS is associated with hepatic venous outflow tract obstruction due to thrombosis along the course of hepatic veins to the junction of inferior vena cava (IVC) with right atrium, clinically presenting acutely with ascites, hepatomegaly and right upper quadrant pain, and chronically with symptoms of portal hypertension and liver failure, which is more common. Studies have reported genetic predispositions causing thrombophilia in such patients.
…”
mentioning
confidence: 99%
“…Studies have reported genetic predispositions causing thrombophilia in such patients. 1,2 Early diagnosis can be done by a Doppler study and liver biopsy to prevent chronic complications of portal hypertension, and progression to hepatic fibrosis and cirrhosis.Management is spearheaded by using non-invasive methods like oral anticoagulants, followed by radiological interventions (stenting/transjugular intrahepatic…”
mentioning
confidence: 99%
See 1 more Smart Citation